Mengelola Referensi Ilmiah dengan Mendeley untuk Penyelesaian Skripsi Mahasiswa: Managing Scientific References with Mendeley for Student Thesis Completion - Ardo Subagjo; Qodri Ali Hasan; Oktaviana Ainun Ratnawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The bibliography/reference is the last part in the preparation of a scientific paper. The function of the bibliography is to provide further information to the readers that the author's work is the result of various sources. Writing a bibliography on the completion of student thesis in the MIPA Education environment of FKIP University of Palangkaraya still makes many mistakes, including several authors' names that are not listed in the bibliography because the preparation has not been automatic / still uses the manual method. This activity will be routinely carried out every semester and several supporting activities, namely making learning media and avoiding plagiarism. The purpose of this activity is for students to get used to it and one day it will be realized that all the results of the student's thesis are required to be submitted to a journal. To achieve this goal, supporting programs are needed every semester. The selected students are all batches of 2019 to 2021 who will prepare thesis and proposal reports. The output of this activity is that 85 students have been skilled in compiling a bibliography and applying it in a thesis, as the first step in helping students to submit their thesis results to an accredited journal.